Pastoralists’ perceptions of forage value and productivity of pasture grasses under different reseeding technologies in Upper Ewaso Nyiro Basin rangelands, Kenya - Mburu, Leonard; Langat, Aisha; Danga, Benjamin (Frontiers in Environmental Science, 2026)
Over 80% of Kenya’s landmass falls under arid and semi-arid lands, where harsh environmental conditions hinder efforts to restore degraded rangelands. Rangeland degradation is a gradual process in which the natural environment is compromised through reduced biological diversity and weakened ecosystem functioning due to anthropogenic and natural causes. This study identified farmers’ preferred pasture grass species and evaluated the effects of different reseeding technologies on growth parameters and dry matter yield of prioritized grasses in Kenya’s Upper Ewaso Nyiro Basin rangelands. Cross-sectional survey results from respondents (n = 118) indicated that broadcasting was the most common reseeding technology (80.8%) while inadequate rainfall was the main critical challenge (73.4%). Based on ranking scores, Cenchrus ciliaris (33.4%), Chloris gayana (20.0%) and Eragrostis superba (18.6%) cumulatively ranked highest for yield, forage yield, ground cover, increased milk production and weight gain. The grasses were subjected to an on-farm randomized complete block design experiment with drilling and broadcasting reseeding technologies under mono- and mixed-cropping systems. Experimental data was subjected to general analysis of variance (ANOVA) using GENSTAT and Tukey’s HSD used to separate significant means (p < 0.05). The total annual rainfall was 741.7 mm while that received from January - June (season 1) and July - December 2021 (season 2) was 316.8 mm and 424.9 mm respectively. Plant density, tiller density, basal cover, dry matter, ash and dry matter yields varied significantly (P < 0.05) across treatments and seasons. Mono-cropped Chloris gayana and its mixed crop with Cenchrus ciliaris consistently achieved higher plant densities, tiller densities and better basal cover. Broadcasted monocropped Eragrostis superba had the lowest productivity (4.55 and 7.51 tons/ha/year), while drilled mixed cropped Cenchrus ciliaris and Chloris gayana had the highest (11.17 and 15.96 tons/ha/year) across the treatments and seasons. These findings indicate that drilling combined with mixed cropping, particularly involving Cenchrus ciliaris and Chloris gayana, should be prioritized in community reseeding initiatives to enhance pasture productivity in arid and semi-arid lands of Upper Ewaso Nyiro Basin.